The question

If the tangent at $(x_1,y_1)$ to the curve $x^3+y^3=a^3$ meets the curve again at a point $(x_2,y_2)$ then prove that $$\frac{x_2}{x_1}+\frac{y_2}{y_1}+1=0$$

My attempt

By differentiating the above expression and finding the slope, the equation of the tangent through the point $(x_1,y_1)$ is $$yy_1^2+xx_1^2=y_1^3+x_1^3$$

As it passes through the point $(x_2,y_2)$, $$y_2y_1^2+x_2x_1^2=y_1^3+x_1^3$$

But I am unable to get the required condition from here.


Given $x^3+y^3=a^3$

Then find $\frac{dy}{dx}=-\frac{x^2}{y^2}$

Then the slope at $(x_1.y_1)$ is $$-\frac{x_1^2}{y_1^2}$$

The slope of the tangent passing through $(x_2,y_2)$ is $$\frac{y_2-y_1}{x_2-x_1}$$

Now lets compare the two equations and we get $$\frac{y_2-y_1}{x_2-x_1}=-\frac{x_1^2}{y_1^2}$$ $$\frac{y_2^3-y_1^3}{x_2^3-x_1^3}\left(\frac{x_1^2+x_1x_2+x_2^2}{y_1^2+y_1y_2+y_2^2}\right)=-\frac{x_1^2}{y_1^2}$$ $$-\frac{x_1^2+x_1x_2+x_2^2}{y_1^2+y_1y_2+y_2^2}=-\frac{x_1^2}{y_1^2}$$ $$x_1^2y_1^2+x_1x_2y_1^2+x_2^2y_1^2=x_1^2y_1^2+x_1^2y_1y_2+x_1^2y_2^2$$ $$x_1^2y_2^2-x_2^2y_1^2=x_1x_2y_1^2-x_1^2y_1y_2$$ $$(x_1y_2-x_2y_1)(x_1y_2+x_2y_1)=x_1y_1(x_2y_1-x_1y_2)$$ $$x_1y_2+x_2y_1=-x_1y_1$$ $$\frac{x_2}{x_1}+\frac{y_2}{y_1}=-1$$ $$\frac{x_2}{x_1}+\frac{y_2}{y_1}+1=0$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.